Thyroid Pathological Consequences Induced by Caffeine in Female Rats - Noora S. ghalib; Abbas A. Khudhair; Kassim F. Abdulkareem (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: this study was designed to investigate the histopathological changes induced by caffeine onthyroid, liver and kidneys in female rats. Caffeine is a central nervous stimulant of methyl xanthine class ofdrugs, it has many hormonal and metabolic effects.Method: twenty-four adult female rats was split in to four equal categories of 6 rats in each group as thefollowing: Group1,control group received distilled water only by oral gavage. Group2, received 35mgofcaffeine solution. Group3, received 75mgof caffeine and Group4, received 150mgof caffeine. Theexperiment continued for 40 days. After 24 hours of the end of experiment, the animals were sacrificed andblood has been withdrawn from vena cava to prepare serum for hormonal analysis, whereas liver, kidneysand thyroid were excised and fixed in formalin solution for histopathological processing.Results: caffeine ingestion cause significant reduction in thyroid function (reduction in T3, T4 and TSH)in all treated groups compared to control group in addition histopathological study show enlargement ofthyroid follicle with thinning of lining epithelium of acini, vacuolation of both renal tubules, hepatocytesand vascular congestion of these organs.Conclusion: Caffeine consumption in high doses causes many histologic and hormonal effects in the studiedorgans.